Peningkatan Komunikasi Mahasiswa melalui Penerapan Model Project Based Learning Berbantuan Aplikasi Quizizz - Firdiawan Ekaputra (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
The development of students’ communication skills remains a central challenge in higher education, particularly within science-based learning contexts that demand active engagement and collaboration. This study aims to examine the effectiveness of implementing a Project-Based Learning (PBL) model assisted by the Quizizz application in enhancing students’ communication skills. Employing a quantitative approach, the research adopts a quasi-experimental design with a one-group pretest–posttest scheme. The study was conducted with 23 students enrolled in the R-001 Chemistry Education class during the Odd Semester of the 2025/2026 Academic Year. Data were collected using a structured questionnaire designed to measure students’ communication skills before and after the instructional intervention. The collected data were subsequently analyzed using a paired-sample t-test to determine the significance of changes in communication performance. The findings reveal a statistically significant improvement in students’ communication skills following the implementation of the Quizizz-assisted PBL model. These results indicate that integrating interactive digital applications within project-based instructional frameworks can effectively foster active participation, collaborative dialogue, and expressive competence among students. The study concludes that Quizizz-assisted Project-Based Learning constitutes a viable pedagogical strategy for strengthening communication skills in higher education learning environments.